Sistem Intelijen Peningkatan Mutu Karet di Kabupaten Cilacap - Budi Dharmawan (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Indonesia is one of the largest rubber exportir in the world. But, the price of rubber from Indonesia is still low because the quality is not within the required standards consumers. Improving quality of rubber is expected to increase farmers' income and region. This study aims to determine the types of strategies involved in improving the quality of rubber in Cilacap regency, Central Java. Analysis using Analytical Hierarchy Process (AHP) and Fuzzy-Multi Expert-Multi Criteria Decision Making (MCDM Fuzzy-ME) obtained the results of selected strategies for improving the quality of rubber in Cilacap District is a technical improvement of rubber cultivation and processing technology improvement.Keywords: Karet, Kualitas, AHP, Fuzzy ME-MCDM